Maintenance Therapy in AML - Reville, Patrick K.; Kadia, Tapan M. (Frontiers in Oncology, 2021)
Recent advances in therapeutics coupled with steady improvements in supportive care for patients with acute myeloid leukemia (AML) have led to improved outcomes. Despite these advances, even in patients that achieve a complete remission with initial therapy high rates of relapse remain a clinical dilemma. For decades, investigators have attempted strategies of maintenance therapy to prolong both remission duration and overall survival in patients with AML. These approaches have included cytotoxic chemotherapy, immunotherapy, hypomethylating agents, and targeted small molecule therapy. Recent strategies, especially with hypomethylating agents have begun to show promise as maintenance therapy in improving clinical outcomes. Ongoing and future studies will continue to elucidate the true role for maintenance therapy options in patients with AML. In this review we summarize prior and ongoing maintenance therapy approaches in AML and highlight some of the most promising strategies.